The Relationship between Students’ Perception of Toxic Relationship and Their Social Interaction at SMKN 15 Bandung City - R. Sumardani; Yuyun Yuningsih; Nur Fadilah Amalia (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The study titled "The Relationship between Students' Perceptions in Preventing Toxic Relationships and Their Social Interactions at SMKN 15 Bandung" was conducted at SMKN 15 Bandung, a vocational school focused on social work. The objectives of this research are to describe and analyze: 1) students' perceptions of toxic relationships at SMKN 15 Kota Bandung, 2) the social interactions at SMKN 15 Bandung, and 3) the relationship between students' perceptions of preventing toxic relationships and their social interactions at the school. The hypothesis states that there is a relationship between students' perceptions of toxic relationships and their social interactions at SMKN 15 Bandung. The research method used is descriptive analysis, and data collection techniques include observation, non-participation, and questionnaires. The population for this study consists of 96 students from SMKN 15 Bandung. Given the relatively similar characteristics of the respondents and their enrollment in the same class, 30% of the population was selected, resulting in 30 respondents. The sampling technique used was random sampling, and the variables were measured using an ordinal scale. The findings indicate a significant relationship between students' perceptions of social work methods and their social skills at SMKN 15 Bandung. The higher the students' perception of social work methods, the higher their social skills at SMKN 15 Bandung.